ANALYSIS OF NEGERI 5 MENARA MOVIE BASED ON ISLAMIC PERSPECTIVE (A LITERATURE STUDY) - Hidayat, Tawvicky (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2024)
This study aims to analyze the film Negeri 5 Menara from an Islamic perspective using a literature review approach. The film, adapted from Ahmad Fuadi's novel, portrays an educational journey in a pesantren (Islamic boarding school) setting, rich with Islamic values. The research focuses on identifying and interpreting the representation of Islamic teachings, such as faith, ethics, Islamic brotherhood (ukhuwah Islamiyah), and the spirit of seeking knowledge. The method employed is content analysis, exploring Islamic themes embedded in the narrative, dialogues, and character development. The findings reveal that Negeri 5 Menara consistently reflects Islamic values, particularly in promoting education, spiritual growth, and interpersonal relationships. The film successfully conveys the universal message of Islam in a way that resonates with modern life. This research is expected to contribute to the development of Islamic studies in popular culture and serve as a reference for future studies in similar fields.